Correction: Effects of crystalline growth on structural and luminescence properties of Ca(10−3x)Eu2x(PO4)6F2 nanoparticles fabricated by using a microwave driven hydrothermal process. Issue 43 (25th October 2018) - Zawisza, Katarzyna; Sobierajska, Paulina; Renaudin, Guillaume; Nedelec, Jean-Marie; Wiglusz, Rafal J.
Abstract : Correction for 'Effects of crystalline growth on structural and luminescence properties of Ca(10−3 x ) Eu2 x (PO4 )6 F2 nanoparticles fabricated by using a microwave driven hydrothermal process' by Katarzyna Zawisza et al., CrystEngComm, 2017, 19, 6936–6949.